The Prevention of Periprosthetic Joint Infections - Küçükdurmaz, Fatih (Open Orthop J, 2016)
Periprosthetic joint infection (PJI) following total joint arthroplasty (TJA) adversely affects patient quality of life and health status, and places a huge financial burden on the health care. The first step in combating this complication is prevention, which may include implementation of strategies during the preoperative, intraoperative, or postoperative period. Optimization of the patient with appreciation of the modifiable and non-modifiable factors is crucial. Preoperative optimization involves medical optimization of patients with comorbidities such as diabetes, anemia, malnutrition and other conditions that may predispose the patient to PJI. Among the intraoperative strategies, administration of appropriate and timely antibiotics, blood conservation, gentle soft tissue handling, and expeditious surgery in an ultra clean operating room are among the most effective strategies. During the postoperative period, all efforts should be made to minimize ingress or proliferation of bacteria at the site of the index arthroplasty from draining the wound and hematoma formation. Although the important role of some preventative measures is known, further research is needed to evaluate the role of unproven measures that are currently employed and to devise further strategies for prevention of this feared complication.